Multi-layer container and manufacturing method thereof
By using butylene glycol propylene alcohol copolymer as the intermediate layer material in a multilayer container and combining co-injection molding technology, the problems of existing multilayer containers being easily whitened and thermally expanded and deformed in high humidity environments are solved, and better airtightness and shape stability are achieved.
Patent Information
- Application Number
- JP2023170501
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-29
- Publication Date
- 2025-04-10
AI Technical Summary
The existing multi-layer containers are made of polyester cellulone (PET). Although they have good mechanical properties and airtightness, they are prone to whitening and thermally expanding and deforming in high humidity environments, and are insufficient airtightness, making it difficult to meet the airtightness requirements for oxygen and carbon dioxide.
Butenediol vinyl alcohol copolymer is used as the intermediate layer material, and co-formed with polyester cellulone (PET) through co-injection molding technology to form a multi-layer container with three-layer structure.
It significantly improves the airtightness, anti-whitening performance and thermal deformation stability of the multi-layer container, meets the needs of use in high humidity environments, and maintains the shape stable after heat treatment.
Smart Images

Figure 2025060022000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a multilayer container and a method for producing the same. [Background technology]
[0002] Polyethylene terephthalate (PET) resin is used in the manufacture of containers for storing food and beverages, etc., because it is inexpensive and has excellent mechanical properties, chemical stability, heat resistance, transparency, etc. From the viewpoint of the preservation of the contents, etc., such containers are required to have gas barrier properties such as oxygen barrier property and carbon dioxide gas barrier property.
[0003] The gas barrier properties of containers made of polyethylene terephthalate resin are improved by thickening the container. However, thickening the container increases the amount of polyethylene terephthalate resin used, which not only increases the weight of the container itself but also leads to an increase in manufacturing costs. Therefore, various ideas have been studied to improve the gas barrier properties without thickening the container. For example, Patent Document 1 describes a plastic container provided with a layer containing a polymetaxylylene adipamide resin as a gas barrier layer. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2007-308155 A Summary of the Invention [Problem to be solved by the invention]
[0005] However, there is room for improvement in the gas barrier properties of containers using polymetaxylylene adipamide resins. Also, containers using polymetaxylylene adipamide resins have problems such as whitening in high humidity environments and dimensional changes when heated.
[0006] Accordingly, an object of the present disclosure is to provide a multilayer container having excellent gas barrier properties, whitening resistance in a high humidity environment, and dimensional stability, and to provide a method for producing the multilayer container. [Means for solving the problem]
[0007] The present inventors have found that when a butenediol-vinyl alcohol copolymer is used as a constituent material for a multilayer container, the gas barrier properties are improved compared to when a conventional polymetaxylylene adipamide resin is used. The inventors also discovered that multi-layer containers using butenediol-vinyl alcohol copolymer as a constituent material have improved whitening resistance and dimensional stability in high humidity environments compared to multi-layer containers using conventional polymetaxylylene adipamide resin as a constituent material for the gas barrier layer. The present disclosure has been completed based on these findings and through further investigation.
[0008] The present disclosure is solved by the following embodiments. <1> A multi-layer container which is a biaxially stretched blow molded product of a multi-layer preform obtained by co-injection molding of butenediol-vinyl alcohol copolymer and polyethylene terephthalate, The multilayer container comprises an inner layer, an intermediate layer, and an outer layer in this order; the inner layer and the outer layer are made of polyethylene terephthalate; A multi-layer container, wherein the middle layer comprises a butenediol vinyl alcohol copolymer. <2> The ratio of the mass of the intermediate layer to the mass of the multilayer container is 2% by mass or more and 8% by mass or less. <1> The multilayer container according to claim 1. <3> The thickness of the body of the multilayer container is 0.10 mm or more and 0.50 mm or less. <1> or <2> The multilayer container according to claim 1. <4> The oxygen permeability measured at a temperature of 23°C and a humidity of 40% is 0.010cc / day·pkg·0.21atm or less. <1> ~ <3> 13. A multilayer container according to any one of claims 1 to 12. <5> After filling the bottle with carbonated water with a gas volume of 3.4 and leaving it for six weeks under conditions of 22°C temperature and 40% RH, the carbon dioxide loss rate is 15% or less. <1> ~ <4> 13. A multilayer container according to any one of claims 1 to 12. <6> After filling the bottle with carbonated water with a gas volume of 3.4 and leaving it for 12 weeks under conditions of 22°C temperature and 40% humidity, the carbon dioxide loss rate is 20% or less. <1> ~ <5> 13. A multilayer container according to any one of claims 1 to 12. <7> co-injection molding a butenediol vinyl alcohol copolymer and polyethylene terephthalate to produce a multi-layer preform; biaxially stretch blow molding the preform; The method for producing a multilayer container comprising the steps of: Effect of the Invention
[0009] The present disclosure can provide a multilayer container that has excellent gas barrier properties, whitening resistance in high humidity environments, and dimensional stability. The present disclosure can also provide a method for producing the multilayer container. [Brief description of the drawings]
[0010] [Figure 1] FIG. 1 is a partial vertical cross-sectional view showing an example of a multi-layer container of the present disclosure. [Diagram 2] 2 is a cross-sectional view of the multilayer container shown in FIG. 1 taken along line II-II. [Diagram 3] FIG. 1 is a partial vertical cross-sectional view showing an example of a multi-layer container of the present disclosure. [Figure 4] FIG. 2 is a front view showing an example of the bottom of a multi-layer container of the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] <Multilayer container> The multilayer container of the present disclosure will be described below with reference to the drawings. In this specification, "upper" and "lower" refer to the upper and lower sides, respectively, of the multilayer container 10 when it is upright (FIG. 1).
[0012] As shown in FIGS. 1 to 3, the multilayer container 10 of the present disclosure includes an inner layer 30, an intermediate layer 20, and an outer layer 40, in this order.
[0013] In one embodiment, the multi-layer container 10 comprises a mouth 11 , a neck 13 disposed below the mouth 11 , and a shoulder 12 disposed below the neck 13 .
[0014] The mouth portion 11 includes a threaded portion 14 that is screwed into a cap (not shown), and a flange portion 17 provided below the threaded portion 14 . The shape of the mouth portion 11 may be any shape known in the art, such as a shape with dimensions conforming to the PCO1810 standard, a screw mouth, a plug mouth, a top seal mouth, or the like.
[0015] The neck 13 is located between the flange 17 and the shoulder 12, and has a generally cylindrical shape with a generally uniform diameter. The shoulder 12 is located below the neck 13, and has a shape whose diameter gradually increases from top to bottom. The body 15 is located below the shoulder 12, and has a polygonal tubular shape with a uniform horizontal cross section from top to bottom.
[0016] The multilayer container 10 has a bottom portion having a recess 31 located at the center and a ground portion 32 provided around the recess 31. The shape of the bottom portion of the multilayer container 10 is not particularly limited, and may have any conventionally known bottom shape.
[0017] The shape of the multilayer container of the present disclosure is not particularly limited, and it is preferable to change it appropriately depending on the type of contents to be filled, etc. For example, when the content is a carbonated drink such as natural sparkling water, a multi-layer container having a petaloid-shaped bottom as shown in FIG. 1 is preferable. Furthermore, when the container is to be heated after being filled with the contents, it is preferable that the container be a multi-layer container having panel portions 41 recessed inwardly on each side of the body portion as shown in FIG.
[0018] The mass ratio of the material constituting the intermediate layer to the mass of the multilayer container is preferably 2% by mass or more and 8% by mass or less, and more preferably 3% by mass or more and 6% by mass or less, which can further improve the gas barrier property of the multilayer container.
[0019] The oxygen permeability of the multi-layer container is preferably 0.010 cc / day·pkg·0.21 atm or less, more preferably 0.005 cc / day·pkg·0.21 atm or less, and even more preferably 0.003 cc / day·pkg·0.21 atm or less. The oxygen permeability is a value measured using an oxygen gas permeability measuring device (product name: OX-TRAN, manufactured by MOCON) under conditions of a temperature of 23° C. and a humidity of 40% RH.
[0020] When the multi-layer container of the present disclosure is filled with carbonated water having a gas volume of 3.4 and left for six weeks under conditions of a temperature of 22°C and a humidity of 40% RH, the carbon dioxide reduction rate is preferably 15% or less, more preferably 10% or less, and even more preferably 8% or less. Furthermore, when the multi-layer container of the present disclosure is filled with carbonated water having a gas volume of 3.4 and left for 12 weeks under conditions of a temperature of 22°C and a humidity of 40% RH, the carbon dioxide reduction rate is preferably 20% or less, more preferably 15% or less, and even more preferably 13% or less. Gas volume is a unit that expresses the amount of carbon dioxide gas contained in a beverage, and is the volume ratio of carbon dioxide gas dissolved in the liquid solvent under standard conditions (1 atmosphere, 20°C). In other words, carbonated water with a gas volume of 3.4 means that 3.4 liters of carbon dioxide gas are dissolved in 1 liter of water.
[0021] The thickness of the body of the multi-layer container is preferably changed appropriately depending on the type of contents to be packed, and is, for example, preferably 0.10 mm or more and 0.50 mm or less, more preferably 0.20 mm or more and 0.45 mm or less, and even more preferably 0.24 mm or more and 0.40 mm or less. The thickness of the shoulder portion of the multi-layer container and the thickness of the ground portion of the multi-layer container are the same as above.
[0022] <Middle Class> The intermediate layer contains a butenediol-vinyl alcohol copolymer. The butenediol-vinyl alcohol copolymer is a resin having butenediol units and vinyl alcohol units as monomer units. The presence of butenediol units together with vinyl alcohol units not only improves gas barrier properties, but also improves whitening resistance and dimensional stability in high humidity environments, which are problems with conventional polymetaxylylene adipamide resins. The butenediol vinyl alcohol copolymer may be a random copolymer or a block copolymer.
[0023] Butenediol vinyl alcohol copolymer can be obtained by hydrolyzing a copolymer obtained by the reaction of 3,4-diacetoxy-1-butene with vinyl acetate. The copolymerization ratio of 3,4-diacetoxy-1-butene and vinyl acetate used as raw material monomers is not particularly limited. For example, it can be [3,4-diacetoxy-1-butene]:[vinyl acetate]=1:99 to 99:1 (molar ratio), it is also preferable to set [3,4-diacetoxy-1-butene]:[vinyl acetate]=10:90 to 90:10 (molar ratio), and it is also preferable to set [3,4-diacetoxy-1-butene]:[vinyl acetate]=20:80 to 80:20 (molar ratio).
[0024] The polymerization degree of the butenediol-vinyl alcohol copolymer is not particularly limited. For example, it can be 100 to 10,000, preferably 200 to 5,000, and more preferably 250 to 3,000. The degree of saponification of the butenediol-vinyl alcohol copolymer is preferably 70 mol % or more, more preferably 80 mol % or more, and even more preferably 90 mol % or more.
[0025] Butenediol-vinyl alcohol copolymers can be obtained from the market, and a preferred example is Nichigo G-Polymer (registered trademark, manufactured by Mitsubishi Chemical Corporation, saponification degree 95.0 mol % or more). Alternatively, butenediol-vinyl alcohol copolymers can be obtained by addition polymerization of 3,4-diacetoxy-1-butene and vinyl acetate in a conventional manner, followed by hydrolysis.
[0026] The resin constituting the intermediate layer may be only butenediol-vinyl alcohol copolymer, but the intermediate layer may contain a resin material other than butenediol-vinyl alcohol copolymer (hereinafter referred to as "other resin material") within a range that does not impair the characteristics of the present disclosure. Examples of other resin materials include polyester resin, (meth)acrylic resin, polyolefin resin, vinyl resin, cellulose resin, nylon resin, phenol resin, polyurethane resin, epoxy resin, ionomer resin, etc.
[0027] The thickness of the intermediate layer is preferably 5 μm or more and 100 μm or less, and more preferably 15 μm or more and 80 μm or less. By setting the thickness of the intermediate layer within the above numerical range, the gas barrier property of the multilayer container can be further improved.
[0028] <Inner and outer layers> The inner and outer layers are composed of polyethylene terephthalate. The polyethylene terephthalate in the present disclosure may be virgin polyethylene terephthalate or recycled polyethylene terephthalate. In addition, the polyethylene terephthalate in the present disclosure may be fossil fuel-derived polyethylene terephthalate or biomass-derived polyethylene terephthalate.
[0029] In this disclosure, "fossil fuel-derived polyethylene terephthalate" is a polycondensate of fossil fuel-derived ethylene glycol and fossil fuel-derived terephthalic acid. In addition, in the present disclosure, "biomass-derived polyethylene terephthalate" is a polycondensate of biomass-derived ethylene glycol and biomass-derived or fossil fuel-derived terephthalic acid.
[0030] In the present disclosure, "virgin polyethylene terephthalate" refers to polyethylene terephthalate that has not been subjected to a recycling process, i.e., unused polyethylene terephthalate. In addition, in the present disclosure, "recycled polyethylene terephthalate" refers to polyethylene terephthalate that has been collected after use of a resin product made of polyethylene terephthalate and reused (recycled).
[0031] Polycondensation of ethylene glycol and terephthalic acid can be carried out by a conventionally known method. Specifically, polyethylene terephthalate can be produced by a general melt polymerization method in which the above-mentioned esterification reaction and / or transesterification reaction of terephthalic acid and ethylene glycol is carried out, followed by a polycondensation reaction under reduced pressure, or by a known solution heating dehydration condensation method using an organic solvent. In addition, the polycondensation reaction is preferably carried out in the presence of a polymerization catalyst.
[0032] The thickness of each of the inner layer and the outer layer is preferably 40 μm or more and 350 μm or less, and more preferably 80 μm or more and 300 μm or less. The thickness of the inner layer and the outer layer means the thickness of the part having the inner layer, the intermediate layer, and the outer layer, i.e., the thickness of the part having a multi-layer structure, and does not mean the thickness of the part having no intermediate layer and being a single layer. For example, in the multi-layer container 10 shown in Fig. 3, the neck part 13, the shoulder part 12, and the body part 15 are made up of multiple layers, so the thickness of the inner layer 30 and the outer layer 40 means the thickness of the inner layer 30 and the outer layer 40 in any part of the neck part 13, the shoulder part 12, and the body part 15, and does not mean the thickness of the mouth part 11, the recessed part 31, and the ground part 32 which are made up of a single layer.
[0033] The inner layer and the outer layer may have the same structure or different structures. For example, the inner layer may be made of virgin polyethylene terephthalate and the outer layer may be made of recycled polyethylene terephthalate.
[0034] <Manufacturing method of multi-layer container> In one embodiment, a method for producing a multi-layer container of the present disclosure includes the steps of co-injection molding a butenediol-vinyl alcohol copolymer and polyethylene terephthalate to produce a multi-layer preform; and a step of biaxially stretch-blow molding the preform.
[0035] The multi-layer container obtained by the above-mentioned production method is a biaxially stretched blow molded product of a multi-layer preform obtained by coinjection molding a butenediol-vinyl alcohol copolymer and polyethylene terephthalate.
[0036] <Co-injection molding process> The preform used in the production of the multilayer container of the present disclosure can be produced by co-injection molding of butenediol-vinyl alcohol copolymer and polyethylene terephthalate. Injection molding of these resins can be carried out using a conventionally known device. The temperature during injection molding can be appropriately set depending on the type of resin. For example, the temperature during injection molding of polyethylene terephthalate is preferably 260°C or more and 310°C or less, more preferably 275°C or more and 300°C or less. The temperature during injection molding of butenediol-vinyl alcohol copolymer is preferably 200°C or more and 240°C or less, more preferably 210°C or more and 230°C or less.
[0037] <Biaxial stretch blow molding> The multilayer container of the present disclosure can be obtained by heating a preform to a surface temperature of preferably 90°C or more and 130°C or less, more preferably 100°C or more and 120°C or less, and then biaxially stretching blow molding it in a mold. The preform may be heated by hot air or infrared rays, and can be heated by using a conventionally known device. Biaxial stretch blow molding of the preform can also be carried out using a conventionally known apparatus, for example, LB01 (trade name) manufactured by KHS. In this way, the equipment used to manufacture conventional containers can be used as is for the co-injection molding process of the resin composition, the heating process of the preform, and the biaxial stretch blow process, so there is no need to prepare new molding equipment for manufacturing the multilayer container of the present disclosure.
[0038] <Other manufacturing methods> In one embodiment, the preform used in producing the multilayer container of the present disclosure can also be produced by compression molding a resin composition in a mold.
[0039] <Application> The contents to be filled into the multilayer container of the present disclosure are not particularly limited, and examples thereof include edible liquids, edible powders or granules, pesticides, pharmaceuticals, and the like. Examples of edible liquids include carbonated drinks such as tea and sparkling water, fruit juices, coffee, milk, various seasonings such as soy sauce, noodle soup, alcoholic beverages such as sake, sports drinks, etc. Edible powders or granules include instant coffee, powdered milk, wheat flour, rice, etc.
[0040] In particular, the multilayer container of the present disclosure has high oxygen barrier properties and is therefore suitable for use with green tea and fruit juice beverages.Furthermore, the multilayer container of the present disclosure has high carbon dioxide gas barrier properties and is therefore suitable for use as a container for filling carbonated beverages. Furthermore, the multilayer container of the present disclosure has dimensional stability when heated, and can therefore withstand heating after being filled with contents, making it suitable for use as a container for selling heated products. EXAMPLES
[0041] The present invention will be described below based on examples, but the present invention is not limited to these.
[0042] <Making bottles for carbonated drinks> [Example 1] As the polyethylene terephthalate constituting the inner layer and the outer layer, SHINPET 5015W (product name, virgin polyethylene terephthalate derived from fossil fuels, manufactured by Shinko Gosei Fibers Co., Ltd.) was prepared. As the butenediol-vinyl alcohol copolymer constituting the intermediate layer, Nichigo G-Polymer (registered trademark) BVE8049P (product name, manufactured by Mitsubishi Chemical Corporation) was prepared. Polyethylene terephthalate was co-injected at 280°C and butenediol vinyl alcohol copolymer was co-injected at 220°C using a multi-layer injection molding machine to obtain a three-layer preform consisting of a layer (inner layer) made of polyethylene terephthalate, a layer (middle layer) made of butenediol vinyl alcohol copolymer, and a layer (outer layer) made of polyethylene terephthalate. The ratio of the mass of butenediol vinyl alcohol copolymer to the total mass of polyethylene terephthalate and butenediol vinyl alcohol copolymer was 4.5% by mass. The mouth of the preform had dimensions corresponding to the PCO1810 standard. The preform obtained as described above was heated to a surface temperature of 107° C. in a blow molding machine (product name: LB01, manufactured by KHS), and then subjected to biaxial stretch blow molding in a mold to be molded into the shape shown in Figures 1 and 2. In this way, the multilayer container of Example 1 was obtained.
[0043] [Comparative Example 1] A multilayer container of Comparative Example 1 was obtained in the same manner as in Example 1, except that a resin composition obtained by mixing polymetaxylylene adipamide resin (product name: Polyamide MXD6 S6007, manufactured by Mitsubishi Gas Chemical Company, Inc.) with 4.5% by weight of an additive (cobalt stearate, manufactured by Wako Pure Chemical Industries, Ltd.) was used instead of butenediol-vinyl alcohol copolymer as the material constituting the intermediate layer, and the resin composition was subjected to co-injection molding at 260°C.
[0044] [Comparative Example 2] A container of Comparative Example 2 was obtained in the same manner as in Example 1, except that SHINPET 5015W was used instead of butenediol-vinyl alcohol copolymer as the material for the intermediate layer, and the SHINPET 5015W constituting the intermediate layer was subjected to co-injection molding at 280°C. The container of Comparative Example 2 had an inner layer, an intermediate layer, and an outer layer all made of the same material, and was essentially a single-layer container.
[0045] The multilayer containers of Example 1 and Comparative Example 1 and the container of Comparative Example 2 all had a weight of 21 g, a full capacity of 388 mL, a total height of 205.58 mm, and a maximum body diameter of 60 mm. In addition, the thicknesses (average values for five samples) at heights of 155 mm, 115 mm, 73 mm, 34 mm, and 15 mm from the ground of the multilayer containers of Example 1 and Comparative Example 1 and the container of Comparative Example 2 were as shown in Table 1.
[0046] <Carbon dioxide gas barrier property evaluation> The multilayer containers of Example 1 and Comparative Example 1 and the container of Comparative Example 2 were filled with carbonated water having a gas volume of 3.4 using a carbonator Pilot Plant BPP-1 (trade name, manufactured by Bixul Co., Ltd.), and then capped. The gas volume in the container after leaving it for 6 and 12 weeks under conditions of a temperature of 22°C and a humidity of 40% RH was measured using a DGV-1 (trade name, manufactured by Bixul Co., Ltd.). The carbon dioxide reduction rate was calculated for each sample by the following formula (1). The results (average value for five samples) are shown in Table 1. Carbon dioxide reduction rate (%) = (gas volume before storage - gas volume after storage) / gas volume before storage × 100 Formula (1)
[0047] [Table 1]
[0048] As is clear from Table 1, the multilayer container of Example 1 suppresses the loss of carbon dioxide gas more than the multilayer container of Comparative Example 1 and the container of Comparative Example 2, and is therefore superior in carbon dioxide gas barrier properties.
[0049] <Preparation of a heating bottle> [Example 2] A multilayer container of Example 2 was obtained in the same manner as in Example 1, except that the mold used during blow molding was changed and molding was performed into the shape shown in Figs.
[0050] [Comparative Example 3] A multilayer container of Comparative Example 3 was obtained in the same manner as in Comparative Example 1, except that the mold used during blow molding was changed and molding was performed into the shape shown in Figs.
[0051] [Comparative Example 4] A container of Comparative Example 4 was obtained in the same manner as in Comparative Example 2, except that the mold used during blow molding was changed and molding was performed into the shape shown in FIGS.
[0052] The multilayer containers of Example 2 and Comparative Example 3 and the container of Comparative Example 4 all had a weight of 21 g, a full capacity of 295 mL, a total height of 132 mm, and a maximum body diameter of 66 mm. In addition, the thicknesses (average values for five samples) at heights of 93 mm, 76 mm, 48 mm, 19 mm and 8 mm from the ground of the multi-layer containers of Example 2 and Comparative Example 3 and the container of Comparative Example 4 were as shown in Table 2.
[0053] <Oxygen gas barrier property evaluation> The oxygen permeability of the multilayer containers of Example 2 and Comparative Example 3 and the container of Comparative Example 4 was measured using an oxygen gas permeability measuring device (product name: OX-TRAN, manufactured by MOCON) under conditions of a temperature of 23° C. and a humidity of 40% RH. The measurement results (average value of two samples) are shown in Table 2.
[0054] <Evaluation of whitening resistance in high humidity environments> The multilayer containers of Example 2 and Comparative Example 3 and the container of Comparative Example 4 were filled with room temperature water so as to leave a head space of 25 mm from the top surface, and then capped. After leaving the container for 2 weeks under conditions of a temperature of 40° C. and a humidity of 90% RH, the appearance of the container was visually observed and evaluated according to the following evaluation criteria. The evaluation results are shown in Table 2. (Evaluation Criteria) A: No whitening of the container was observed. B: Whitening of the container was observed.
[0055] <Dimensional stability evaluation> The multilayer containers of Example 2 and Comparative Example 3 and the container of Comparative Example 4 were filled with room temperature water so as to leave a head space of 25 mm from the top surface, and then capped. The container was stored in a can warmer (product name: TW75-C3, manufactured by Nippon Heater Kiki Co., Ltd.) with the water temperature kept at 70°C. The dimensional changes of the containers were measured after one week, two weeks, and three weeks of storage. A Mitutoyo Digimatic Height Gauge, Code No. 192-663, was used to measure the dimensional change in the overall height. A Mitutoyo Depth Gauge, Model ID-C1012XBD, was used to measure the dimensional change in the bottom depth. The measurement results (average value of five samples) are shown in Table 2.
[0056] [Table 2]
[0057] As is clear from Table 2, the multilayer container of Example 2 has a smaller oxygen permeability and is superior in oxygen gas barrier property than the multilayer container of Comparative Example 3 and the container of Comparative Example 4. Moreover, it is also clear that the multilayer container of Example 2 does not show any whitening in a high humidity environment, and is excellent in whitening resistance. Furthermore, it is also clear that the multilayer container of Example 2 has a smaller amount of dimensional change upon heating than the multilayer container of Comparative Example 3 and the container of Comparative Example 4, and is therefore more excellent in dimensional stability. [Explanation of symbols]
[0058] 10:Multilayer container 11: Mouth 12:Shoulder 13: Neck 14: Screw section 15: Torso 17: Flange part 20: Middle class 30: Inner layer 31: Recess 32: Grounding part 40: Outer layer 41: Panel section
Claims
1. A multi-layer container which is a biaxially stretched blow molded product of a multi-layer preform obtained by co-injection molding of butenediol-vinyl alcohol copolymer and polyethylene terephthalate, The multilayer container comprises an inner layer, an intermediate layer, and an outer layer in this order; the inner layer and the outer layer are made of polyethylene terephthalate; A multi-layer container, wherein the middle layer comprises a butenediol vinyl alcohol copolymer.
2. 2. The multilayer container according to claim 1, wherein the ratio of the mass of the intermediate layer to the mass of the multilayer container is 2 mass % or more and 8 mass % or less.
3. 3. The multilayer container according to claim 1, wherein the thickness of the body of the multilayer container is 0.10 mm or more and 0.50 mm or less.
4. 3. The multilayer container according to claim 1, which has an oxygen permeability of 0.010 cc / day·pkg·0.21 atm or less as measured at a temperature of 23° C. and a humidity of 40% RH.
5. 3. The multilayer container according to claim 1 or 2, which is filled with carbonated water having a gas volume of 3.4 and left for six weeks under conditions of a temperature of 22° C. and a humidity of 40% RH, and exhibits a carbon dioxide reduction rate of 15% or less.
6. 3. The multilayer container according to claim 1 or 2, which is filled with carbonated water having a gas volume of 3.4 and left for 12 weeks under conditions of a temperature of 22° C. and a humidity of 40% RH, and has a carbon dioxide gas reduction rate of 20% or less.
7. co-injection molding a butenediol vinyl alcohol copolymer and polyethylene terephthalate to produce a multi-layer preform; biaxially stretch blow molding the preform; The method for producing a multilayer container comprising the steps of:
Citation Information
Patent Citations
Plastic container having gas barrier layer
JP2007308155A